PENINGKATAN PENGETAHUAN TENTANG PENCEGAHAN KECELAKAAN KERJA PADA PEKERJA DI SMK SEHATI KARAWANG - Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Muhidin, Muhidin; Widhiantika, Wieke (LP2M STP Mataram, 2024)
Workplace accidents are one of the risks faced by workers in vocational education environments, including at Vocational High Schools (SMK). This program aimed to increase knowledge and awareness of occupational health and safety (OHS) among staff at SMK Sehati Karawang. The training was conducted through several stages, including awareness sessions, general OHS training, accident handling simulations, and continuous monitoring and evaluation. The results showed that the majority of participants were highly satisfied with the program, with 50% stating they were very satisfied, 30% satisfied, 15% fairly satisfied, and 5% dissatisfied. The program significantly increased awareness of the importance of using personal protective equipment (PPE) and understanding risk management in the SMK environment. According to monitoring results, the application of OHS improved significantly, particularly in the use of PPE and quick response to emergency situations. This program was supported by previous studies showing that comprehensive OHS training can reduce workplace accidents by up to 70%. With continuous support and evaluation, this program is expected to serve as a model for effective OHS implementation in other vocational schools